2014
DOI: 10.1177/2167696814536165
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Experience of Latino Young Adults in College and Their Perceptions of Values About Sex Communicated by Their Parents and Friends

Abstract: This study examines the values in Latino young adults' perceptions of messages about sex during their formative years and their current level of sexual exploration and sexual assertiveness. Latino young adults in college (N ¼ 218) rated the prevalence of four types of messages they heard from parents and friends: Sex is only for marriage (procreational), sex is only appropriate in a loving relationship (relational), sex is for pleasure (recreational), and the sexual double standard. Relational sex was most pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 53 publications
5
48
1
Order By: Relevance
“…Yet several recent studies suggest that families of origin may continue to play an important role in emerging adults' lives as they negotiate their identities and relationships in a context of growing independence (Hardie and Stanik 2012;Heisler 2014;Manago et al 2015). This influence is especially likely among college-attending emerging adults who do not leave home, but live with or near family throughout their young adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet several recent studies suggest that families of origin may continue to play an important role in emerging adults' lives as they negotiate their identities and relationships in a context of growing independence (Hardie and Stanik 2012;Heisler 2014;Manago et al 2015). This influence is especially likely among college-attending emerging adults who do not leave home, but live with or near family throughout their young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies of emerging adults have explored how families of origin shape sexual and romantic relationships post-adolescence (Arnold et al 2013;Heisler 2014;Manago et al 2015;Trinh et al 2014). In support of social learning theory, these studies show that parents influence emerging adult relationships via direct or indirect messages.…”
Section: Sexual and Romantic Scripts In Emerging Adulthoodmentioning
confidence: 94%
“…The Heterosexual Script (α female peers = .80, α male peers =.80) consists of 6 items (e.g., “It is worse for a woman to sleep around than it is for a man”). A version of this measure has been used in previous research (Fletcher et al, in press; Manago et al, in press; Trinh et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…They also vary in their content. Analyses documenting the specific sexual themes communicated indicate that college students report occasional or frequent discussions regarding the importance of relationships, acceptance of casual sex, and endorsement of gendered sexual roles, and infrequent discussions regarding abstinence until marriage (Fletcher, Ward, Thomas, Foust, Levin, & Trinh, in press; Manago, Ward, & Aldana, in press; Trinh, Ward, Day, Thomas, & Levin, 2014). Similarly, Morgan and Zurbriggen (2012) found that college students report valuing mutual respect, romantic relationships, consent, and sexual pleasure.…”
Section: Pluralistic Ignorance: Reality Versus Peer Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation